Asset Management System (AMS) - Wan Nurul Nabihah, Wan Suhaimi (2019)
The purpose of this project thesis is to explain how the Asset Management System ( AMS) will improve the manual approach in asset auditing document process. This thesis will briefly explain the advantage and disadvantage of the system. The idea of the creation this system is to improve the old method in preparing the asset document. The old method will exceed the time to prepare the complete asset auditing document that follow government of treasury standard. The other problem is by manual approach the synchronization during the document preparation also will not aligned because it will need more than one people to managed all document.Because of the problem stated AMS has been purpose to be developed to enhance the quality of document preparing process. This system be able to store all the stock history in the database. The approval process also can be done by the online method. The report of the asset auditing will be auto generate by the information retrieve from the database.During the development process the iterative model will be used to guide in developing the system. The purpose of choosing this methodology is because its flexible and suitable for big system.The expected result of this system is it will generate the accurate data from the database.Inclusion, the system will computerize the manual document in order to fulfil the client requirement. The AMS is expected to be the modern technology that replace the manual method. This thesis has attached with Software Requirement Specification (SRS) , Software Development Document (SDD) and also User Acceptance Test (UAT)